Transitivity Analysis of Jokowi and Prabowo Campaign Speech in Indonesian Presidential Election 2019 - Khairani Ade Guswita; Suhardi Suhardi (Indonesian Journal of EFL and Linguistics, 2020)
This study of the transitivity system aims to identify and describe the type of transitivity, namely the process, participant, and circumstance which appeared in Jokowi and Prabowo campaign speech in 2019. The method used was qualitative method and researcher as key instrument in this study. The method used in collecting data was Metode Simak which proposed by Sudaryanto (2018). Data collected were analyzed by using the theory of Halliday (1985), namely Systemic Functional Linguistics (SFL) which focused on transitivity system. The results of the study based on data analysis show that there are 24 data or about 32% material process as dominant process that found in Jokowi campaign speech, the most dominant participant is actor that found about 15.1% or 23 data , and time as the most dominant of circumstance that found about 21.4% or 9 data. Whereas in Prabowo's campaign speech found that the most dominant process that used is material process about 37.5% or 30 data with the most dominant participant, namely actor and goal that have the same amount of data about 28 data or 18.2%, the circumstance type which is the most dominant used namely place about 11 data or 26.8%. The most dominant transitivity process used by the two presidential candidates shows that the two presidential candidates try to convey things related to the activities or actions that will be done by each presidential candidate if they are elected to become president of Indonesia in 2019-2024 period.